Collaborative 3D Terrain Editing Application - K.M. Nasution, Mahyuddin; Timanta Tarigan, Jos; Jaya, Ivan; Melvani Hardi, Sri; Sitorus, Syahriol (International Journal of Engineering and Technology, 2018)
In 3D content creation, developing a terrain may be time consuming due to most of current 3D applications require a vast terrain. In this paper, we introduce a collaborative terrain editor that allows multiple users to collaborate in real time. The objective of the application is to increase the productivity in developing a vast terrain in 3D environment. The application is based on a client server architecture where each editor applications are connected to a single server that collects and distributes the editing process done by each user. We perform our test in a local area network environment with multiple clients connected to a server and observe the performance and the usability of the software. The test results show the system is capable to perform real-time collaborative terrain editing with insignificant delay. Moreover, most of our users agree that using the system may increase the speed in 3D terrain creation.
Keywords: Collaborative Work; Computer Graphic; Client-Server Systems